(untitled) (Bangladesh Journal of Botany, 2025)
In Algeria, the number of citrus trees ranks second after olive trees, but their economic importance places them clearly at the top of fruit production. The nematode Tylenchulus semipenetrans attaches to citrus roots and causes slow citrus dieback. The chemical nematicides used in agriculture have eco-toxicological effects. On the other hand, bio-nematicides do not have harmful effects on the ecosystem. In this context, the present study on essential oils from aromatic plants, specifically from the Lamiaceae family, uses two species: Thymus algeriensis and Rosmarinus officinalis. Some ligands derived from essential oils have an inhibitory effect on Acetyl-CoA Carboxylase, an enzyme responsible for the biosynthesis of fatty acids in Tylenchulus semipenetrans. Using molecular modeling methods, including molecular docking with the Molecular Operating Environment (MOE) software, the study reveals for the first time that linalool, a major component of Thymus algeriensis, is a functional inhibitor of Acetyl-CoA Carboxylase activities and can be used as an effective bio-insecticide against Tylenchulus semipenetrans to protect citrus trees. Bangladesh J. Bot. 54(1): 145-152, 2025 (March)